DEVELOPMENT AND CLINICAL TESTING OF AN ALGORITHM FOR THE SELECTION OF A LOCAL HEMOSTATIC AGENT FOR TRAUMATIC LIVER INJURIES - Bobokulova, Sh.A.; Ganzhiev, F.Kh.; Achilova, O.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. The choice of a local hemostatic agent for liver injuries in emergency surgery remains empirical and often subjective, despite the existing variety of drugs. The lack of a formalized approach reduces the reproducibility of results and increases the risk of complications. Purpose. To develop an algorithm for selecting a hemostatic agent based on the type of injury, the nature of bleeding and the surgical suitability of the drug, as well as to conduct its clinical testing. Materials and methods. The study included 44 patients with traumatic liver injuries of I–III degrees. In the control group (n=23), the drug was chosen randomly, in the main group (n=21) – according to the proposed algorithm. Results. The algorithm significantly reduced the average duration of bleeding from 158.2±19.4 to 78.6±13.7 seconds (p<0.001), and the volume of blood loss from 314±56 ml to 142±31 ml (p<0.001). The frequency of repeated application decreased from 39.1% to 9.5%. In 100% of cases, the use of the algorithm made it possible to avoid technical difficulties. Conclusion. The developed algorithm for selecting a hemostatic agent for liver injuries makes it possible to increase the reproducibility of surgical solutions and the clinical effectiveness of treatment, especially in conditions of limited time and unstable anatomical situation.